Decolonising mathematics education: Teachers’ initial experiences of using ethnomathematical games in the intermediate phase - Safura Meeran (Interdisciplinary Journal of Sociality Studies)
The African Agenda 2063 strives to attain the goals of peace and prosperity, and to do so, there must be a process of political liberation and decolonisation. In the South African context, decolonisation involves transforming the mathematics curriculum to one that is African by employing cultural approaches such as ethnomathematics. However, South African mathematics teachers still rely on Eurocentric methods for teaching mathematics. To decolonise mathematics in the Intermediate Phase, a project was initiated that utilised indigenous games for teaching mathematics. This paper aims to identify whether such efforts to decolonise mathematics education will be accepted or rejected by the mathematics teachers involved in this study. The paper is framed by the Critical Mathematics Pedagogy Theory. A qualitative case study approach was employed to collect data through a focus group interview with ten mathematics teachers who teach in rural and semi-rural areas of KwaZulu-Natal, South Africa. The findings demonstrate that ethnomathematical games encourage mathematics learning, that teachers’ initial apprehensions gave way to enthusiasm, that learners were excited to play and learn, and that teachers found it effortless to integrate mathematical concepts such as addition, subtraction, multiplication, factorisation, and quadrilaterals with the indigenous games of Morabaraba, Tshetershere, Diketo, and Kgati. Recommendations include that mathematics educational policies incorporate ethnomathematics as a policy directive and that teachers receive training in alternative cultural pedagogical practices for teaching mathematics, such as the use of ethnomathematics. Future research endeavours should focus on finding avenues to sustain ethnomathematics in the classroom.